Pneumatic Powered Kerrison Rongeur in Spine Surgery Can Benefit Patient and Surgeon: Surgical Tips - Obana, Kyle; Kato, Kenneth; Illingworth, Kenneth; Andras, Lindsay; Skaggs, David (Journal of the Pediatric Orthopaedic Society of North America, 2021)
Spinal deformity surgeons are at increased risk of overuse injuries. The use of power instruments has been incorporated to reduce the rate of occupational injuries and increase efficiency of surgery without increasing risk to the patient. The pneumatic powered Kerrison rongeur minimizes the force a surgeon must apply and theoretically may increase precision. The purpose of this paper is to review the technique and safety of the pneumatic Kerrison in pediatric spine deformity surgery.